Komunikasi Politik Elit NU dan Muhammadiyah dalam Pilkada Kediri (Jurnal Kajian Media, 2018)
This research seeks to analyze the political communication run by elite Nahdlatul Ulama (NU) and Muhammadiyah in the election of Mayor and Vice Mayor (Pilwali) Kediri Year 2013 ago. Organizationally, neither NU nor Muhammadiyah declared its involvement in the Kediri City Pilwali process. But personally, at the elite level, there is a role performed by each of these institutions. This study was studied using descriptive qualitative method with purposive selection technique of informant accompanied by triangulation of source as technique of examination of data validity. The political communication carried out by both NU and Muhammadiyah is a political communication based on the Pareto stratification which divides the community groups that have the advantage to govern and who have no advantages whatsoever. NU has an elite stratification consisting of elites who have the advantage to govern and represent by kyai and elite who have no superiority to govern by being described as NU daily administrators on the management of Tanfidziyah. While the majority of Muhammadiyah elites have the capability as an elite that has an advantage with consideration of the influence resulting from political communication conducted by the elites. The results of this study indicate that political communication that occurs is a representation of an elite circulation process that results in an elite shift as a form of elite substitute shrewdness in shifting the previous strong elite's position through shifting values by placing influential groups in political contestation as a group capable of transferring power of the previous group. Keywords: Nahdlatul Ulama, Muhammadiyah, Elit.